Chromium evaporation and oxidation characteristics of alumina-forming austenitic stainless steels for balance of plant applications in solid oxide fuel cells. (15th June 2021) - Zhou, Lingfeng; Zeng, Zhipeng; Brady, Michael P.; Leonard, Donovan N.; Meyer, Harry M.; Yamamoto, Yukinori; Li, Wenyuan; Collins, Greg; Liu, Xingbo
Abstract: The chromium (Cr) evaporation behavior of several different types of iron (Fe)-based AFA alloys and benchmark Cr2 O3 -forming Fe-based 310 and Ni-based 625 alloys was investigated for 500 h exposures at 800 °C to 900 °C in air with 10% H2 O. The Cr evaporation rates from alumina-forming austenitic (AFA) alloys were ~5 to 35 times lower than that of the Cr2 O3 -forming alloys depending on alloy and temperature. The Cr evaporation behavior was correlated with extensive characterization of the chemistry and microstructure of the oxide scales, which also revealed a degree of quartz tube Si contamination during the test. Long-term oxidation kinetics were also assessed at 800 to 1000 °C for up to 10, 000 h in air with 10% H2 O to provide further guidance for SOFC BOP component alloy selection. Highlights: Cr evaporation and oxidation behaviors of AFA alloys were studied. Cr evaporation rates from AFA alloys were much lower than chromia-forming alloys. Continuous alumina layer formed on AFA alloys remained steady after test. Possible Si contamination and Cr deposited on alumina tubes were discussed.